Spatial Analysis of Poverty Phenomenon and Handling it in the District of Hit in the Period (2007-2020) - Salim, Nadia Talib (Journal of Tikrit University for Humanities, 2023)
This research addresses the issue of poverty in the district of Hit, examining the regional variation of poverty indicators at the district level and proposing strategies for its mitigation. This research seeks to discover several conceptualizations of poverty, its typologies, and the underlying factors contributing to its occurrence. Additionally, it intends to determine the levels of poverty and the indicators connected with it. The research also seeks to discover the methods used to address the issue in order to draw conclusions and provide suggestions that may help alleviate the poverty problem experienced by many impoverished families. The research indicates a progressive rise in the poverty rate within the district, with a recorded increase from 30.2% in 2007 to 36.8% in 2020. This signifies that almost one-third of the district's population lives below the poverty threshold. Furthermore, it is worth noting that the poverty rate exhibits variation among different districts. Al-Baghdadi had the greatest poverty rate, standing at 72.4%, whilst the city of Hit demonstrated the lowest poverty rate. The poverty rate in the district was found to be 16.9%, with a poverty gap of 8.9%. This suggests that the poverty level is not severe, and it is recommended to implement policies that enhance the capabilities of the poor. These policies should contribute to reducing the poverty rate and enable individuals to engage in various activities. The study emphasizes the importance of aligning economic policies, social programs, and development initiatives with the district's capabilities. This alignment is crucial for increasing income levels and reducing poverty rates.